(3GdfGSN hGdefShNs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3bGd eQ Ydi QVi Gddg Yfg Ydi bGVi abGd dg CJYQa GdfGSN ef GdefShN bGd dG bGd gdcJ hCgdcJ s
(3BNQgG (B:s
(3ShQI GdENdGU hGdYdb hGdfGS GNJda GdeaSQhf ai JfRjdgf hcdgf eMce djS Hgf fGSN hdG efShN GfJgi s
(3GdfSNI HgG MhGTs
(3hbO UMMJ gPg GdfSNI Ydi GdCUd Gdefbhdg efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B615s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs